Hubungan Lama Menderita Diabetes Melitus dengan Kadar Prothrombin Time (PT) dan Activated Partial Thromboplastin Time (APTT) - Nikma Nikma (UPPM Poltekkes Kemenkes Ternate, 2022)
Background: Hyperglycemia, hyperinsulinemia, and insulin resistance have been observed in various studies as the causes of changes in various components that play an important role in hemostasis. Purpose:This study aims to analyze the relationship between the duration of Type 2 DM and the hemostatic conditions of PT and APTT. Methods: This study belongs to an observational study with a cross sectional approach using plasma blood samples that have been filled with the anticoagulant Na citrate 3.2% taken from patients who have met the research sample criteria. The number of samples was 30, all of whom were patients with type 2 diabetes mellitus. Results: Between the duration of DM and PT, the results were not significant (p > 0.05), the PT results here described the extrinsic pathway of blood clotting. Meanwhile, between the duration of DM and APTT, the test results obtained a significant relationship (p < 0.05), this illustrates that there is a significant effect on the intrinsic pathway with the duration of DM